The psychology of leadership : new perspectives and research - Messick, David M.; Kramer, Roderick M. (Roderick Moreland), 1950- (Organization and management series (Routledge (Firm)), 2005)
In this book, some of the world's leading scholars come together to describe their thinking and research on the topic of the psychology of leadership. Most of the chapters were originally presented as papers at a research conference held in 2001 at the Kellogg School of Management of Northwestern University. The contributions span traditional social psychological areas, as well as organizational theory; examining leadership as a psychological process and as afforded by organizational constraints and opportunities. The editors' goal was not to focus the chapters on a single approach to the stud.